Tooth Wear in Relation to Selected Salivary Variables among a Group of Older Adults - Yas, Baydaa Ahmed (Journal of Baghdad College of Dentistry, 2016)
Background: Tooth wear is one of the most concerning problems of the current dental practice especially among older subjects. The aim of this study is to determine the severity of tooth wear and its relation with selected salivary variables (salivary pH and vitamin C level) among a group of older adults in Mosul city/Iraq. Materials and methods: All subjects (30 subjects) of both gender tookpart in the current study; sixteen of them were older adults (55-65 years) and compared with fourteen middle-aged adults (30-40 years) at Textile factory in Mosul city/Iraq. Unstimulated salivary samples were collected and salivary pH was immediately measured. Salivary vitamin C level was determined colormetrically. Severity of tooth wear was determined according to Hansson and Nilner (1975) classification. Results: Results showed that all severity scores of tooth wear revealed higher percentage among older adults than middle-aged adults. Also all tooth segment types revealed higher percentage of tooth wear among older adults than middle-aged adults. Moreover regarding the highest score of tooth wear by subjects, higher percentage of tooth wear was found among older adults than middle-aged adults. Concerning the total sample results disclosed that wear of enamel only revealed higher percentage than one or more teeth worn into dentine and one or more teeth worn up to 1/3 of the crown. Also in the total sample the incisor region showed higher percentage of tooth wear while the least tooth wear percentage was found in the molar region. In both age groups no significant correlations were found between salivary pH and vitamin C with the highest score of tooth wear. Conclusion: Tooth wear is more severe among older subjects. Further study is needed with larger sample size and more precise index that measure the etiology of tooth wear.